UPAYA PENYELESAIAN KONFLIK PEMBAGIAN TANAH WARISAN YANG BELUM DIBAGI WARIS DI KABUPATEN SLEMAN - , Burhan Albar; , Prof. Dr. Maria S.W. Sumardjono, S.H., MCL., MPA. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research aims to identify solutions on the statement problems regarding the conflict resolution efforts of undistributed allocation of inheritance land, they are: the factors that cause conflict of undistributed allocation of inheritance land and the method of resolution if dispute or conflict emerges between the heirs regarding the allocation of inheritance land. In regard to the above problems, this research utilized primary data from respondents and resource person as well as secondary data. As a legal research, secondary data were obtained from primary legal materials in the form of laws and regulations as well as secondary legal material to support the primary legal materials. The data were then analyzed qualitatively and presented descriptively. The research result shows that, first, the occurrence of conflict of undistributed allocation of inheritance land was caused by the unfulfilled sense of justice of each heir, and different opinion or interests of the heirs. Factors which trigger conflicts are high selling price of land, location and type of land, inheritance registration fee, delay of allocation, a large number of heirs, and the existence of inheritance law pluralism. Second, conflict resolution of allocation of inheritance land can be taken through in-court system and out âof-court settlement. Conflict resolution through out-of-court settlement can be conducted through negotiation and mediation. Meanwhile, conflict resolution through in-court system is by filing a lawsuit in order to be resolved with judge decision or by decision based on the mediation in the court.